SEASONAL DYNAMIC OF TERMITE FORAGING (ISOPTERA) IN CAT TIEN NATIONAL PARK (SOUTH VIETNAM) - Irina, Semenyuk; Nguyen, Thi Van (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
Foraging activity of five termite species, namely Macrotermes carbonarius (Hagen), M. gilvus (Hagen), M. malaccensis (Haviland), Hypotermes obscuriceps (Wasmann), Hospitalitermes bicolor (Haviland), was studied in Cat Tien National Park for two years with monthly performed route counting of open forages. Chosen model species differed in ecological preferences, life history and the nesting type. Termites community showed foraging activity all round the year. Foraging activity despite the original hypothesis did not correlate significantly with precipitation level and soil temperature measured monthly. Most of species increased foraging activity in dry months, but decreased it in months with heavy rains. In rainy season, most of species demonstrated not only night time foraging activity typical for Asian termites, but also were actively foraging during the daytime. During the dry season, foraging activity happened only in night time. Termite species showed different strategies and adaptations to abiotic conditions, which allow the community to maintain decomposing activity all round the year.